Mega vs. Macro Influencers: Narrative Analysis of Motul Promotions on Instagram - Rizal Perdana, Buwana; Jannah, Miftahul (COMMENTATE: Journal of Communication Management, 2025)
The development of digital technology has transformed the landscape of marketing communication, particularly through social media, which has become a dominant channel for influencer marketing strategies. This research offers novelty by analyzing the differences in soft-selling and hard-selling communication styles employed by mega- and macro influencers in promoting Motul-branded vehicle oil on Instagram, an automotive industry context rarely explored in Indonesia. Using a descriptive qualitative approach with thematic analysis, this study identifies recurring patterns in promotional narratives. Data were collected through content documentation, semi-structured interviews with the Motul brand manager, and online narrative questionnaires. The study operationalizes 'promotional narratives' by analyzing four core elements: personal experience, emotional framing, technical explanation, and Call to Action (CTA). The findings indicate that soft selling is more effective in building emotional attachment, while hard selling drives information seeking. The contextual insights from this research enrich the digital marketing communication literature in the automotive sector and provide a practical contribution for marketers in designing targeted collaboration strategies with influencers that align with audience segments and campaign goals.